2009
DOI: 10.1159/000211676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of either Tibolone or Continuous Combined Transdermal Estradiol with Medroxyprogesterone Acetate on Coagulatory Factors and Lipoprotein(a) in Menopause

Abstract: Background/Aim: The aim of this prospective controlled study was to compare the effects of two therapies for menopause on factor VII (FVII) and hemostatic variables. Methods: Postmenopausal women were assigned to receive one of the following treatments: transdermal estradiol (TTS E2; 50 μg) combined in a continuous sequential regimen with oral medroxyprogesterone acetate (MPA; 10 mg/day for 12 days) (group A; n = 20), tibolone (2.5 mg/day) (group B; n = 21) or placebo (group C; n = 19). Sixty women completed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 127 publications
0
15
0
1
Order By: Relevance
“…In a recent doubleblind placebocontrolled trial among postmenopausal women, treatment with letrozole, an oral nonsteroidal aromatase inhibitor, resulted in more than a doubling of mean Lp(a) levels (112). Treatment with tibo lone, a synthetic steroid drug, at a dose of 2.5 mg/day for a year in postmenopausal women significantly decreased Lp(a) concentration by 28% (113).…”
Section: Exercise and Bmimentioning
confidence: 99%
“…In a recent doubleblind placebocontrolled trial among postmenopausal women, treatment with letrozole, an oral nonsteroidal aromatase inhibitor, resulted in more than a doubling of mean Lp(a) levels (112). Treatment with tibo lone, a synthetic steroid drug, at a dose of 2.5 mg/day for a year in postmenopausal women significantly decreased Lp(a) concentration by 28% (113).…”
Section: Exercise and Bmimentioning
confidence: 99%
“…Lp(a) levels are under a strong genetic regulation and are not affected by changes in lifestyle and physical characteristics, as well as currently available lipid‐lowering drugs. However, sex hormones constitute an important exception and studies have shown menopause‐related changes in Lp(a) concentration and Lp(a)‐lowering effect by testosterone administration and Lp(a)‐increasing effect by orchidectomy in men, or hormone‐replacement therapy in women . In view of this, a better understanding of the role of Lp(a) in PCOS has attracted attention.…”
Section: Discussionmentioning
confidence: 99%
“…shown menopause-related changes in Lp(a) concentration and Lp(a)-lowering effect by testosterone administration and Lp(a)increasing effect by orchidectomy in men, 25,26 or hormone-replacement therapy in women. 14,[27][28][29][30][31][32] In view of this, a better understanding of the role of Lp(a) in PCOS has attracted attention. One study in Turkish women reported a higher mean Lp(a) level in PCOS women compared to healthy controls (25Á2 mg/dl vs 16Á7 mg/dl, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In general, tibolone seems to induce a greater reduction in Lp(a) in comparison with HRT when transdermal oestrogen (50 μg/d) is used and similar or greater reduction when oral oestrogen is used (0.625 mg/d of CEE or 2 mg of 17β‐estradiol) . The exact mechanisms for tibolone‐induced reductions in Lp(a) have not been clarified.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%